Entomological indices of malaria transmission in Chikhwawa district, Southern Malawi - Mzilahowa, Themba (BioMed Central, 2012)
BACKGROUND: Although malaria is highly prevalent throughout Malawi, little is known of its transmission dynamics. This paper describes the seasonal activity of the different vectors, human biting indices, sporozoite rates and the entomological inoculation rate in a low-lying rural area in southern Malawi. METHODS: Vectors were sampled over 52 weeks from January 2002 to January 2003, by pyrethrum knockdown catch in two villages in Chikhwawa district, in the Lower Shire Valley. RESULTS: In total, 7,717 anophelines were collected of which 55.1% were Anopheles gambiae sensu lato and 44.9% were Anopheles funestus. Three members of the An. gambiae complex were identified by PCR: Anopheles arabiensis (75%) was abundant throughout the year, An. gambiae s.s. (25%) was most common during the wet season and Anopheles quadriannulatus occurred at a very low frequency (n=16). An. funestus was found in all samples but was most common during the dry season. Anopheles gambiae s.s. and An. funestus were highly anthropophilic with human blood indices of 99.2% and 96.3%, respectively. Anopheles arabiensis had fed predominantly on humans (85.0%) and less commonly on cattle (10.9%; 1.2% of blood meals were of mixed origin). Plasmodium falciparum (192/3,984) and Plasmodium malariae (1/3,984) sporozoites were detected by PCR in An. arabiensis (3.2%) and An. funestus (4.5%), and in a significantly higher proportion of An. gambiae s.s. (10.6%)(p<0.01). All three vectors were present throughout the year and malaria transmission occurred in every month, although with greatest intensity during the rainy season (January to April). The combined human blood index exceeded 92% and the P. falciparum sporozoite rate was 4.8%, resulting in estimated inoculation rates of 183 infective bites/ person per annum, or an average rate of ~15 infective bites/person/month. CONCLUSIONS: The results demonstrate the importance of An. gambiae s.s., An. arabiensis and An. funestus in driving the high levels of malaria transmission in the south of Malawi. Sustained and high coverage or roll out of current approaches to malaria control (primarily insecticide-treated bed nets and indoor residual house spraying) in the area are likely to reduce the observed high malaria transmission rate and consequently the incidence of human infections, unless impeded by increasing resistance of vectors to insecticides.